PENGARUH PROFITABILITAS, PERTUMBUHAN ASET , UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Galuh Aninditiyah; Bambang Widjanarko Susilo; Vivi Kumalasari Subroto; Galuh Aditya; Aftuqa Sholikatur Rohmania; Haryo Kusomo (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2024)
This study aims to analyze the influence of profitability, asset growth, and company size on the capital structure of companies listed on the Indonesia Stock Exchange. Capital structure is a crucial element in financial management that affects funding decisions and company risks. The analysis method used was multiple regression, with a sample during the period 2014-2018. The results showed that profitability had a significant negative effect on capital structure, indicating that high-profit companies tended to use less debt. Asset growth, on the other hand, has a significant positive effect on capital structure, suggesting that fast-growing companies are more likely to capitalize on debt. Meanwhile, the size of the company does not show a significant influence on the capital structure. These findings provide important insights for managers in formulating effective and efficient funding strategies, and emphasize the need to consider internal and external factors in decision-making related to capital structure.